A Coping Strategy in Adolescent with Parental Divorce - Aghniacakti, Ainindita; Halida, Hilda (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
Parental divorce is one of the triggers of long-term stress and can have a negative impact on children. Therefore, adaptive coping strategies are needed in dealing with these stressors. This study aims to explore the coping strategies used by adolescents in dealing with parental divorce. The method in this study is qualitative with a phenomenological approach. The participants in this study amounted to 4 people with an age range of 18-20 years. Based on the results of the interview, there are five themes of coping strategies that emerged, namely: (1) Expressing emotions; (2) Establishing communication with parents, (3) Seeking help and support from others, (4) Interpreting parental divorce more positively, and (5) Accepting parental divorce. This research is based on the real experiences of the participants and the findings raise awareness about choosing adaptive coping strategies to minimize the negative impact of parental divorce. The results of this study can be used as a benchmark by families and practitioners to help divorced families.